A Formal Framework for Prototyping Executable Semantics in ATL - Boronat, Artur (Theory and Practice of Model Transformation, 2018)
ATL is a well-established model transformation language both in industry and in academia, where it is used as a reference language for studying different types of model transformations and their properties. In this paper, we discuss current limitations of ATL’s in-place semantics that hamper its application for modelling and verifying systems and propose a new in-place semantics for ATL that enables it as a specification language for simulating and verifying EMF-based systems. Our approach is based on FMA-ATL, an executable specification of a large excerpt of ATL in Maude, which has been augmented with the new in-place semantics so that Maude’s verification tools can then be used both to perform bounded model checking of invariants and to model check LTL formulas in the resulting system models, where appropriate. Furthermore, FMA-ATL uses ATL as front-end language and it can be reusedas-is for verification, including its tool support.